Assessing Vaccines and Vaccination Programmes in the Field (Italian Journal of Public Health, 2009)
Background: The impact of universal vaccination programmes in terms of reduction of disease burden is notquestioned very much in the scientific community. Nevertheless assessing safety and efficacy of vaccinationproducts in the field is an essential part of the success of any vaccination programme. In addition to that,there are several aspects of vaccination programmes that have to be evaluated and carefully assessed in orderto improve the overall quality of vaccination programmes.Methods: Several different epidemiological methods have been developed during the last decades for thesepurposes. A critical review of innovative epidemiological methods used for assessing vaccines in the field wasundertaken.Results: Availability of innovative methods and progress made in the field of health informatics allow easyevaluation of large volumes of information.Conclusions: In addition to scientific and technical support, political commitment is required in order toincrease the amount of resources available for public health professionals. International organisations canplay an important role at the EU level.
Keywords: vaccines; vaccination programmes; safety; effectiveness; Europe